Dyslipidemia and electrolyte metabolism in essential hypertensive North Indians - Naz, Qulsoom; Serajuddin, M.; Verma, N. S.; Mehdi, A. Ali; Patel, M. L.; Anjum, Baby (International Journal of Research in Medical Sciences, 2017)
Background: In the present study we are going to evaluate lipid profile and Electrolytes levels (Sodium, Potassium in Serum & Urine) in Essential Hypertensive and in healthy controls in North Indian Population. Methods: A total of 210 age and sex matched E. hypertensive & healthy controls were included in our study from outpatient department (OPD) of Medicine in King George Medical University, Lucknow, India. First group consist of 110 subjects were known E. hypertensive patients (B.P ≤ 139/89mm of Hg). Another group is control group consist of 100 subjects who were healthy controls (B.P ≤ 120/80mm of Hg) with no history of hypertension. Fasting venous blood sample was collected from all the subjects in plane vacationer and the sample was centrifuged for the estimation of lipid profile & electrolyte i.e. Sodium (N+) & Potassium (K+). Lipid profile was measured with an automated analyzer (Biochem) & Electrolytes was measured using ion-selective electrolyte auto-analyzer in the Clinical lab of biochemistry in KGMU. Results: After analyzing results almost control subjects had normal lipid profile level. In patients of E. hypertension there was a highly significant increase in serum Total Cholesterol (p˂0.0001), LDL-Cholesterol (p˂0.0001) & Triglycerides (p˂0.001). HDL-Cholesterol (p˂0.03) is also significant as compare to controls. Not significant difference was found in serum sodium & potassium level. The Urinary Na+ levels were significantly lower in E. hypertensive patients when compared to controls while Urinary K+ levels were not significant. Conclusion: So we conclude that dyslipidemia is associated with essential hypertension this may due to the genetic predisposition, secondary lifestyles, fatty food consumption, saturated fat, cholesterol in the food increase the blood cholesterol and saturated fat is the main culprit. Essential hypertensive is linked with increased Na+, K+ - ATPase activity and increased renal tubular sodium reabsorption.